Perceived Maternal Discrimination and Adverse Perinatal Outcomes Among Black Women [A136]. (May 2022) - Adeyeye, Adeola; Ard, Quantrilla; Da Cunha Godoy, Lucas; Shields, Andrea; Campbell, Winston; Cooper, Shontreal
Abstract : INTRODUCTION: The purpose of this study is to determine if perceived maternal discrimination among Black women with varying levels of education impacts adverse perinatal outcomes such as preterm delivery and low birth weight. METHODS: We surveyed a cohort of 400 Black women between January and April 2019 who delivered an infant in the United States within the last 5 years after institutional review board approval. Participants were recruited through advertisements on social media. Inclusion criteria were participants who self-identified as a Black female, 18 years or older, and fluent in English. The validated Jackson, Hogue, Phillips Contextualized Stress Measure Survey was used. Scores were obtained from the sum of the responses. Scores were divided into tertiles to denote low, moderate, and high stress levels. Data was analyzed using Fisher's exact test and pairwise comparison if the Fisher's test was statistically significant. A P value <0.05 was considered statistically significant. RESULTS: From the 400 Black women surveyed, 107 completed surveys were returned and analyzed. The mean age of the respondents was 38 (26–49). The majority of respondents had either a college (42.9%) or professional degree (48.5%). Approximately 58% reported household incomes greater than 90, 000. Of women with moderate to high levels of perceived racism, 13.51% and 15.79% had a preterm delivery, P =.02. CONCLUSION: Perceived racism and indicators of general stress were associated with preterm delivery and low birth weight. These findings provide further evidence that psychosocial factors may play an important role in birth outcome disparities among Black women.